2009
DOI: 10.1063/1.3096414
|View full text |Cite
|
Sign up to set email alerts
|

Unusual products observed in gas-phase WxOy−+H2O and D2O reactions

Abstract: Addition of H(2)O and D(2)O to small tungsten suboxide cluster anions W(x)O(y)(-) (x = 1-4; y < or = 3x) was studied using mass spectrometric measurements from a high-pressure fast flow reactor. Within the WO(y)(-) mass manifold, which also includes WO(4)H(-), product masses correspond to the addition of one to three H(2)O or D(2)O molecules. Within the W(2)O(y)(-) cluster series, product distributions suggest that sequential oxidation W(2)O(y)(-) + H(2)O/D(2)O --> W(2)O(y+1)(-) + H(2)/D(2) occurs for y < 5, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 25 publications
4
61
1
Order By: Relevance
“…Our optimized geometrical parameters compare well with crystal structure suggesting that the tungsten cluster optimization is fairly accurate to derive the structural and thermodynamic parameters. The infrared spectrum of W 6 O 19 2-is shown in Figure 11 2-is shown in Figure 12a. The density plot clearly reveals the delocalization of the anionic electron density over three inequivalent subunits of W-O cluster moieties of the W 6 O 19 2-system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our optimized geometrical parameters compare well with crystal structure suggesting that the tungsten cluster optimization is fairly accurate to derive the structural and thermodynamic parameters. The infrared spectrum of W 6 O 19 2-is shown in Figure 11 2-is shown in Figure 12a. The density plot clearly reveals the delocalization of the anionic electron density over three inequivalent subunits of W-O cluster moieties of the W 6 O 19 2-system.…”
Section: Resultsmentioning
confidence: 99%
“…16 Various kinds of metal-carbon cage clusters were explored in great detail by Guo et al 17 Molecular level details of small WO clusters on oxidative catalysis have been reported by Johnson et al 18 recently. Rothgeb et al 19 reported the unusual reactivity of small anionic WO clusters with H 2 O and D 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in Figure 4b, a low-intensity product peak with mass corresponding to Mo 4 36,37 To compare those rate constants to the rates of Mo x O y − + ROH reactions, the same analysis will be applied here. Individual oxide peaks in the x = 2 and 3 manifolds of Mo x O y − vary as a function of alcohol (ROH) number density present in the reactor.…”
Section: Methodsmentioning
confidence: 98%
“…The HO−H bond dissociation energy is 1.17 eV higher than the CH 3 −OH bond dissociation energy, which may explain why abstraction products were not observed in the cluster−water reactivity studies. 36,37 The most predominant product peak, …”
Section: Methodsmentioning
confidence: 99%
“…11,30,31 Cluster anions were generated in an ablation source using the second harmonic output of a Nd:YAG laser (5 mJ/pulse) focused onto a target prepared from pressed cerium powder (Sigma-Aldrich Co., St. Louis, MO). The resulting plasma coalesced and cooled and was swept through the 2.5 cm long, 0.3 cm diameter reaction channel in a pulse of ultra-highpurity helium issued from a solenoid-type molecular beam valve (BV1), synchronized with the laser.…”
Section: Experimental Methodsmentioning
confidence: 99%